Muon-spin rotation studies of the flux lattice in kappa-(BEDT-TTF)(2)Cu(SCN)(2) - Lee, S; Blundell, S; Pratt, F; Pattenden, P; Forgan, E; Sasaki, T; Aegerter, C; Hunt, M; Chow, K; Hayes, W; Singleton, J; Keller, H; et al. (1997)
Muon spin rotation (mu SR) studies of the vortex lattice in the superconductor kappa-(BEDT-TTF)(2)Cu(SCN)(2) have revealed a crossover from a quasi-2d to a vortex-line lattice structure for fields below a characteristic field B-cr. The mu SR-lineshapes measured from the vortex-line lattice have allowed a re-evaluation of the in-plane penetration depth.